3D-Printed Cold Preservation Device in Renal Autotransplantation for the Treatment of a Patient With Renal Artery Stenosis - Cui, Dong; Wu, Bin; He, Dali; Wang, Yanen; Jiao, Yong; Zhang, Bo (Frontiers in Bioengineering and Biotechnology, 2022)
Percutaneous transluminal angioplasty (PTRA) is a common treatment method for renal vascular disease (RVD). However, PTRA may not be effective in patients with abnormal vascular disease. Renal autotransplantation (RAT) has been used as an alternative therapy for these diseases. Restrictions due to intracorporeal kidney cold preservation, and the renal function of intracorporeal RAT was not as well protected compared with open operation. We developed this technique of 3D printed polylactide (PLA) cold jackets for laparoscopic complete intracorporeal RAT on the purpose to better protect renal function and determined the feasibility of this novel procedure. The procedure was successfully applied in a 51-year-old female with bilateral renal artery stenosis. The operation time was five hours, and the blood loss was 200 mL. The patient’s blood pressure remained constant throughout the operation, and the pressure was maintained at 120-140/70-90 mmHg without antihypertensive drugs at one week after the operation. B-ultrasound showed that the blood flow signal of the transplanted kidney was normal and the boundary between the skin and medulla was clear. The patient was discharged 2 weeks after surgery. One year postoperatively, Doppler ultrasound of the autotransplant showed that the transplanted kidney was normal in size and shape. Radionuclide renal dynamic imaging revealed that the glomerular filtration rate (GFR) of the transplanted kidney was 36.9 mL/min. 3D-printed polylactide (PLA) cold jackets for laparoscopic complete intracorporeal RAT are a safe and effective method for the treatment of renal artery stenosis and represent a feasible method of preserving the renal function of severe renal artery stenosis patients; however, the technology is still at the exploratory stage and has room for further improvements.